Mechanical Alloying and Subsequent Heat Treatment of Ag-Zn Powders - Ordonez, S; Serafini, D (2013)
Microstructural evolution during mechanical alloying of Ag and Zn, and subsequent heat treatments were investigated. The mechanical alloying was carried out in a SPEX 8000D miller. The microstructural characterization was obtained by X-ray diffraction (XRD), transmission electron microscopy (TEM) and scanning electron microscopy (SEM). The thermal behavior was studied using differential scanning calorimetry (DSC). Based on the results obtained, it can be concluded that at the early stages of milling was possible to detect the É, ?, ??, ? solid solutions and remaining Zn. Later, the É, ?, ?? and Zn phases disappeared while the Zn concentration of the ? solid solution was strongly increased. After 7.2 ks of milling, the mechanical alloying process reached a steady state. During this period, both the composition and crystallite size of the ? solid solution remained practically unchanged. On the other hand, subsequent heat treatments of milled powders showed that the ? solid solution could also be obtained by the combination of mechanical alloying and heat treatment. Finally, the evolution of the microstructure during milling and annealing was combined to propose an optimal processing route in order to obtain a ? solid solution. © 2013 The Nonferrous Metals Society of China.